2024
DOI: 10.1186/s12912-024-02005-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with clinical nurse’s mental health: a qualitative study applying the social ecological model

Qiang Yu,
Chongmei Huang,
Yusheng Tian
et al.

Abstract: Background The prevalence of burnout, depression, and anxiety among Chinese nurses was 34%, 55.5%, and 41.8% respectively. Mental health problems have significant impacts on their personal well-being, work performance, patient care quality, and the overall healthcare system. Mental health is influenced by factors at multiple levels and their interactions. Methods This was a descriptive qualitative study using phenomenological approach. We recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Social Cognitive Theory emphasizes the dynamic and reciprocal interaction between the individual, their behavior, and the environment, including key concepts such as self-efficacy, observational learning, and reinforcement [5]. The Ecological Model considers multiple levels of influence on behavior, including intrapersonal, interpersonal, organizational, community, and policy factors [6]. These theories and models provide a foundation for understanding behavior change and informing the design of effective interventions to promote healthier behaviors, and researchers and practitioners often draw on multiple models to guide their approaches [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Social Cognitive Theory emphasizes the dynamic and reciprocal interaction between the individual, their behavior, and the environment, including key concepts such as self-efficacy, observational learning, and reinforcement [5]. The Ecological Model considers multiple levels of influence on behavior, including intrapersonal, interpersonal, organizational, community, and policy factors [6]. These theories and models provide a foundation for understanding behavior change and informing the design of effective interventions to promote healthier behaviors, and researchers and practitioners often draw on multiple models to guide their approaches [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that sleep quality has a significant impact on health ( 15 , 16 ), especially among HCWs ( 17 , 18 ). Poorer sleep quality may lead to lower work productivity ( 19 ), more medical errors ( 20 ) and burnout ( 21 ) for HCWs. Research has identified that both personal (such as education and socio-economic status) ( 22 , 23 ) and work-related factors (like job type and workload) ( 24 ) influence HCWs’ sleep quality.…”
Section: Introductionmentioning
confidence: 99%